Postexercise hypotension and blood lipoprotein changes following swimming exercise - Tanaka, H.; Sommerlad. S. M.; Renzi, C. P.; Barnes, J. N.; Nualnim, N. (Biomechanics and Medicine in Swimming XI, 2010)
It is not known whether an acute bout of swimming exercise results in similar changes in risk factors for coronary heart disease. To address this question, a total of 20 apparently healthy subjects were studied. Each subject performed 3 experimental sessions (time control, running exercise, and swimming exercise) separated by at least one week. Brachial blood pressure did not change after the 3 sessions. However, both running and swimming produced significant decreases in ankle blood pressure compared with the time control (P<0.05). There were no significant changes in cholesterol or triglycerides after the swimming or running sessions. We concluded that postexercise responses in blood pressure and blood cholesterol do not appear to be different between running and swimming.